EKSTRA KURIKULER SENI SEKOLAH DASAR DI PEKANBARU - Zufriady, Zufriady (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
Primary school extracurricular activities are additional activities of the compulsory learning process that must be possessed bystudents so that they can develop their talents, skills, and also characterize elementary school children as a provision in theirlives. The purpose of this study is to describe the extracurricular activities of elementary school art in Pekanbaru. This study usesdescriptive qualitative research methods. The extracurricular activities in Pekanbaru consist of drum band, tambourine, dance,nasyid, choir, painting. some schools run well and some only run if there are competitions or school events.